2008
DOI: 10.1186/1471-2164-9-476
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput cell-based screening reveals a role for ZNF131 as a repressor of ERalpha signaling

Abstract: Background: Estrogen receptor α (ERα) is a transcription factor whose activity is affected by multiple regulatory cofactors. In an effort to identify the human genes involved in the regulation of ERα, we constructed a high-throughput, cell-based, functional screening platform by linking a response element (ERE) with a reporter gene. This allowed the cellular activity of ERα, in cells cotransfected with the candidate gene, to be quantified in the presence or absence of its cognate ligand E2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous reports, including ours, demonstrated that ZNF13 acts as a repressor of estrogen receptor ␣-mediated trans-activation (30,42,43). In addition, we previously reported that the SUMOylation of ZNF131 negatively regulates estrogen receptor ␣-mediated signaling and estrogen-induced cell proliferation in breast cancer cells (30).…”
Section: Discussionmentioning
confidence: 50%
“…Previous reports, including ours, demonstrated that ZNF13 acts as a repressor of estrogen receptor ␣-mediated trans-activation (30,42,43). In addition, we previously reported that the SUMOylation of ZNF131 negatively regulates estrogen receptor ␣-mediated signaling and estrogen-induced cell proliferation in breast cancer cells (30).…”
Section: Discussionmentioning
confidence: 50%
“…However, whether FBI-1 could regulate the signaling of nuclear receptors such as AR and ER was still unclear [9,11,12,21]. Recently, zinc finger protein 131 (ZN131), a typical member of the BTB/ POZ family, was found to function as a repressor of estrogen receptor alpha (ERa) and repress ligand-dependent ERa transactivitation and the expression of pS2, an ERa target gene [22]. PLZF, the homolog of FBI-1, is an androgen-responsive gene and can inhibit LNCaP proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…on Estrogen Signaling-Next, we examined whether ZNF131 negatively regulates estrogen signaling, based on a previous report that ZNF131 inhibits ligand-dependent trans-activation by ER␣ (10). ER␣-positive MCF-7 breast cancer cells were transfected with a luciferase reporter plasmid containing four tandem EREs in the presence or absence of HA-ZNF131.…”
Section: Sumo Modification Potentiates Negative Effect Of Znf131mentioning
confidence: 99%
“…Whereas ZNF131 was previously reported to suppress ER␣ target gene expression (10), its molecular and regulatory mechanism has not yet been characterized. Here, we identify ZNF131 as a target for SUMOylation and report that hPc2 is its SUMO E3 ligase.…”
mentioning
confidence: 99%
See 1 more Smart Citation